Physical activity in relation to health status, quality of life and compliance with World Health Organization recommendations in patients with axial spondyloarthritis - M. Carbo; B. Hilberdink; D. Paap; F. Wink; T. Vliet Vlieland; S. van Weely; A. Spoorenberg; S. Arends (Arthritis Research & Therapy)
Abstract Objective Physical activity (PA) has well-established benefits and is a fundamental component in the management of axial spondyloarthritis (axSpA). Our objective was to evaluate (1) compliance with the World Health Organization (WHO) PA recommendations, (2) specific types and duration of PA performed by patients, and (3) association of PA with health status and quality of life (QoL) in two large Dutch cohorts of axSpA patients. Methods In the GLAS and LUMC patient cohorts, the modified (m) and original Short QUestionnaire to ASess Health-enhancing PA (SQUASH) was used to determine fulfillment of recommendations on aerobic and muscle-strengthening PA. Univariable and multivariable linear regressions were used to analyze PA in relation to health status (ASAS-HI) and QoL (ASQoL). Results In the GLAS (n = 148) and LUMC (n = 193) cohorts, patients were 49 ± 13 and 56 ± 14 years old, time since diagnosis was median 11 (IQR 5–21) and 23 (IQR 8–35) years and 59% and 69% were male, respectively. In total, 72% and 77% patients fulfilled the aerobic component, 40% and 36% the muscle-strengthening component and 37% and 34% both components of the WHO PA recommendations. Walking, cycling and gym or aquatic exercises were done most often. Higher (m)SQUASH score was associated with better outcome in disease-related health status (ASAS-HI) and QoL (ASQoL), also after adjusting for age, sex, BMI, disease activity and physical function. Conclusion The minority of axSpA patients fulfilled the WHO PA recommendations. Patients were less likely to meet the muscle strengthening component than the aerobic component. A higher level of PA was associated with better disease-related health status and QoL.